C5 electric car: failure of a marketing strategy - Smith, PR (Henry Stewart Talks, 2018)
This case study examines the failure of Britain’s first electric car, the C5. The C5 car failed due to poor marketing strategy and production ended after just nine months. Had the C5 positioned itself differently, it may not have been remembered as one of the biggest disasters in technology history.